2009
DOI: 10.1074/jbc.m807345200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of RanBP9 in BACE1 Processing of Amyloid Precursor Protein and Amyloid β Peptide Generation

Abstract: Accumulation of the amyloid ␤ (A␤) peptide derived from the proteolytic processing of amyloid precursor protein (APP) is the defining pathological hallmark of Alzheimer disease. We previously demonstrated that the C-terminal 37 amino acids of lipoprotein receptor-related protein (LRP) robustly promoted A␤ generation independent of FE65 and specifically interacted with Ran-binding protein 9 (RanBP9). In this study we found that RanBP9 strongly increased BACE1 cleavage of APP and A␤ generation. This pro-amyloido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
144
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(149 citation statements)
references
References 42 publications
4
144
1
Order By: Relevance
“…Although RanBP9 has previously been implicated in the promotion of cell death, the mechanisms of such activity are unknown. 25 We have previously shown that RanBP9 accelerates APP, LRP, and b1-integrin endocytosis, simultaneously leading to increased Ab generation in vitro and in vivo 6,7 and disruption of focal adhesions. 9 As such, our observation that RanBP9 activates/dephosphorylates cofilin is consistent with the known role of the integrin-LIMK pathway in the inactivation/phosphorylation of cofilin, although the Slingshot pathway cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although RanBP9 has previously been implicated in the promotion of cell death, the mechanisms of such activity are unknown. 25 We have previously shown that RanBP9 accelerates APP, LRP, and b1-integrin endocytosis, simultaneously leading to increased Ab generation in vitro and in vivo 6,7 and disruption of focal adhesions. 9 As such, our observation that RanBP9 activates/dephosphorylates cofilin is consistent with the known role of the integrin-LIMK pathway in the inactivation/phosphorylation of cofilin, although the Slingshot pathway cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that increased RanBP9 expression promotes BACE1 processing of APP and Ab generation by scaffolding APP/BACE1/LRP complexes together and accelerating APP endocytosis. 6 To determine whether RanBP9-induced cell death is dependent on its ability to promote Ab generation, we treated HT22 cells with or without 5 mM g-secretase inhibitor, DAPT, for 24 h under normal cell culture conditions (10% FBS). In the absence of Ab oligomer treatment, no detectable Annexin V or PI staining could be observed in control empty vector-transfected cells in the presence or absence of g-secretase inhibition ( Figure 6).…”
Section: Wt Ranbp9 Tgmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of LRP expression causes reduced APP internalization and Ab secretion (Ulery et al 2000;Pietrzik et al 2002;Cam et al 2005), leading to the conclusion that endocytosis of LRP is coupled to APP internalization and processing, and Fe65 acts as a functional linker between APP and LRP in modulating endocytic APP trafficking (Pietrzik et al 2004). In addition, Ran-binding protein 9 promotes APP interaction with APP and facilitates APP internalization in a Fe65-independent manner (Lakshmana et al 2009). Finally, the type I transmembrane protein sorLA/LR11 (a member of the VPS10p-domain receptor family), which functionally interacts with cytosolic adaptors GGA and PACS-1, regulates Ab production by acting as a Golgi/TGN retention factor for APP (Andersen et al 2005;Offe et al 2006;Schmidt et al 2007).…”
Section: Endocytic App Sorting and Ab Productionmentioning
confidence: 99%